Seeking green grass: Strong sustainability for golf and turfgrass. Issue 1 (24th February 2021) - Fitzpatrick, Robbie; White, Rehema; Matthews, Iain
Abstract: Despite practical advances in many areas of sustainability, golf still faces a number of complex, interlinked challenges heading into the future. Using strong sustainability as a critical interpretive lens, this paper radically reimagines what golf is, what golf does, and what golf can be for current and future generations and identifies some possibilities to be found through the theory and practice of sustainable development. For the sake of current and future generations, golf must explore means of minimizing resource inputs, minimizing waste outputs, optimizing use of renewable energy and maximizing player participation and satisfaction. To do this, golf requires a paradigm shift from efficiency to sufficiency supported by big thinking, moral responsibility and radical renovations in its practices, technologies and values. Using the fundamental principles of sustainability, we begin to envision an overhaul of golf as part of broader societal transformations. In short, this paper poses a provocation for "thinking otherwise" about golf and sustainability and opens fertile ground for turfgrass practitioners and researchers to begin cultivating more resilient and sustainable fields of play.